The Qualitative Measurement towards Emotional Feeling of Design for Product Development - Syaifoelida F.; Megat Hamdan M.A.M.; Murrad M.; Aminuddin H. (Institute of Physics Publishing, 2023)
Customer satisfaction; Integrated circuits; Product development; Sales; Stars; Design evaluation; Emotional feeling; Human interactions; Kansei Engineering; Level of satisfaction; Qualitative measurements; Research and development; Technical requirement; Product design